Live birth following the first mutation specific pre-implantation genetic diagnosis for haemophilia A - Michaelides, Katerina; Tuddenham, Edward G. D.; Turner, Cathy; Lavender, Ben; Lavery, Stuart A. (Thrombosis and Haemostasis, 2006)
Haemophilia A is an X-linked, recessive, inherited bleeding disorder which affects 1 in 5000 males born worldwide. It is caused by mutations in the FactorVIII (F8) gene on chromosome Xq28. We describe for the first time two mutation specific, single cell protocols for pre-implantation genetic diagnosis (PGD) of haemophilia A that enable the selection of both male and female unaffected embryos. This approach offers an alternative to sexing, frequently used for X-linked disorders, that results in the discarding of all male embryos including the 50% that would have been normal. Two families witha history of severe haemophilia A requested carrier diagnosis and subsequently proceeded to PGD. The mutation in family1 isa single nucleotide substitution c. 5953C>T, R1966X in exon 18 and in family 2, c. 5122C>T, R1689C in exon 14 of the F8 gene. Amplification efficiency was compared between distilled water and SDS/proteinase K cell lysis (98.0%, 96/98 and 80%, 112/140 respectively) using 238 single lymphocytes. Blastomeres from spare IVF cleavage-stage embryos donated for research showed amplification efficiencies of 83.3% (45/54) for the R1966X and 92.9% (13/14) for the R1689C mutations. The rate of allele dropout (ADO) on heterozygous lymphocytes was 1.1% (1/93) for R1966X and 5.94% (6/101) for R1689C mutations. A single PGD treatment cycle for family1 resulted in two embryos for transfer but these failed to implant. However, with family 2, two embryos were transferred to the uterus on day 4 resulting in a successful singleton pregnancy and subsequent live birth of a normal non-carrier female.
Keywords: FVIII; haemophilia A; inherited bleeding disorder; preimplantation genetic diagnosis